Causes of mode effects: Separating out interviewer and stimulus effects in comparisons of face-to-face and telephone surveys - Caroline Roberts; Annette Jäckle (University of Essex, Institute for Social and Economic Research (ISER), 2012)
We attempt to isolate the causes of mode effects on measurement in a comparison of face-to-face and telephone interviewing, distinguishing between effects caused by differences in the type of question stimulus used in each mode (audio vs. visual) and effects caused by other differences between the modes, notably, the presence or absence of the interviewer. We use data from an experiment conducted in the context of the European Social Survey. Differences in the stimulus did not lead to differential measurement error, but the presence or absence of the interviewer did. Telephone respondents were far more likely to give socially desirable responses than face-to-face respondents.
Keywords: C83; 330; showcards; measurement; satisficing; social desirability bias